Strongly reducing magnesium(0) complexes - Rösch, Bastian; Gentner, Thomas; Eyselein, Jonathan; Langer, Jens; Elsen, Holger; Harder, Sjoerd (Nature, 2021)
A complex of a metal in its zero oxidation state can be considered a stabilized, but highly reactive, form of a single metal atom. Such complexes are common for the more noble transition metals. Although rare examples are known for electronegative late-main-group p-block metals or semimetals1-6, it is a challenge to isolate early-main-group s-block metals in their zero oxidation state7-11. This is directly related to their very low electronegativity and strong tendency to oxidize. Here we present examples of zero-oxidation-state magnesium (that is, magnesium(0)) complexes that are stabilized by superbulky, monoanionic, β-diketiminate ligands. Whereas the reactivity of an organomagnesium compound is typically defined by the nucleophilicity of its organic groups and the electrophilicity of Mg2+ cations, the Mg0 complexes reported here feature electron-rich Mg centres that are nucleophilic and strongly reducing. The latter property is exemplified by the ability to reduce Na+ to Na0. We also present a complex with a linear Mg3 core that formally could be described as a MgI-Mg0-MgI unit. Such multinuclear mixed-valence Mgn clusters are discussed as fleeting intermediates during the early stages of Grignard reagent formation. Their remarkably strong reducing power implies a rich reactivity and application as specialized reducing agents.
CRIS-Team Scopus Importer:2021-05-14